Inside Mecca [ - Amirani, Taghi; Bredar, John B.; David, Keith; Khan, Yasir; Mahbob, Ismail; Mandhlazi, Khalil; Mehdi, Anisa; O'Leary, Fidelma (National Geographic special, 2003)
The most intimate and three-dimensional documentation of the annual pilgrimage to Mecca. "Inside Mecca" follows three Muslims from very different backgrounds as they embark on an epic five-day reaffirmation of faith and quest for salvation. Witness the personal stories of the pilgrims and the mental preparation, physical strain and spiritual ecstasy they encounter on their pilgrimage of faith